Bound Improving Sequences: A Tool for Discrete Programming - Bárcia, Paulo (2019)
The purpose of this note is to report a new tool for discrete programming: Bound improving sequences. It consists on the construction of a sequence of bounds that, under appropriate conditions, converges in a finite number of steps to the optimal value of the objective function of the Problem studied. As a byproduct an optimal solution for that problem is produced. For the case of 0-1 LP's such a sequence can be efficiently computed. Examples, geometric interpretations and computational experience reports for this case are given.